1990
DOI: 10.1155/1991/45352
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐Independent Selection of T15 Idiotype During B‐Cell Ontogeny In Mice

Abstract: focus assays were detected in the spleens of neonatal mice as early as 4 days after birth. The earliest anti-PC B cells were T15-. T15 foci-forming B cells were first detected 6 days after birth and expanded rapidly to constitute greater than 80% of the total PC-specific foci by day 10. Injection of heat-killed S. pneumoniae (R36A) into neonatal mice resulted in priming of the antibody response to PC, with an idiotype profile reflecting that of precursors of foci-forming B cells at the time of antigen administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 9 publications
0
28
1
Order By: Relevance
“…Murine B cells expressing transgenes for group I anti-PC Abs have also been reported to display altered activation, trafficking, and peripheral accumulation (19), which may suggest that these Ig transgene-expressing B cells were being selected by an autoantigen. However, until our recent demonstration of PC neo-determinants on apoptotic cells and on atherosclerosis-associated oxidation-specific Ags (20), the true nature of such postulated selecting self-Ags was unsuspected (21).…”
Section: Discussionmentioning
confidence: 99%
“…Murine B cells expressing transgenes for group I anti-PC Abs have also been reported to display altered activation, trafficking, and peripheral accumulation (19), which may suggest that these Ig transgene-expressing B cells were being selected by an autoantigen. However, until our recent demonstration of PC neo-determinants on apoptotic cells and on atherosclerosis-associated oxidation-specific Ags (20), the true nature of such postulated selecting self-Ags was unsuspected (21).…”
Section: Discussionmentioning
confidence: 99%
“…6B) (Vakil et al, 1991) clones increase in frequency while others decline our facility. (Sigal et al, 1977;Stohrer and Kearney, 1984;Vakil et al, 1991 …”
Section: Introductionmentioning
confidence: 87%
“…In a similar experiment, mice were stration of soluble idiotype-bearing immunoinjected with 5/g of DEX on days 2, 7, 14, or 21 globulins would block signaling through B-cellafter birth and challenged with R36A and DEX at 8 associated idiotypes on the precursors of endoweeks of age (Fig. 6B) (Vakil et al, 1991) clones increase in frequency while others decline our facility. (Sigal et al, 1977;Stohrer and Kearney, 1984;Vakil et al, 1991 …”
Section: Introductionmentioning
confidence: 90%
“…This model suggests a possible mechanism by which multispecific T15 + B-cell clones may have been positively selected. These clones, which react not only with OxLDL and bacterial PC but also with apoptotic cells, may have been selected by interaction with apoptotic debris at sites of B-cell development in fetal liver and bone marrow (15), in a process that could involve receptor editing before or during the proliferation of specific B cells. Although the present authors have previously shown (16,17) that deliberate immunization of hypercholesterolemic rabbits or mice expressing high levels of OxLDL lessens atherosclerosis, the role of these autoantibodies against OxLDL needs more evaluation.…”
Section: Natural Antibodies To Phosphorylcholinementioning
confidence: 99%